Modelling a quantitative ensilability index adapted to forages from wet temperate areas - Martinez-Fernandez, A.; Soldado, A.; de-la-Roza-Delgado, B.; Vicente, F.; Gonzalez-Arrojo, M. A.; Argamenteria, A. (Spanish Journal of Agricultural Research, 2013)
Forage ensilability mainly depends on dry matter (DM), water soluble carbohydrates (WSC) and buffer capacity (BC) values at harvest time. According to these parameters, and based on a collection of 208 forages of known ensilability characteristics including short and long term meadows for grazing, italian ryegrass, maize, triticale, soybean, faba bean crops, and samples coming from cereal-legume associations, the objective of this study has been to define a quantitative ensilability index (EI) based on a relationship between DM, WSC and BC contents at harvest date, adapted to the characteristics of fodder from wet temperate areas. For this purpose, a discriminant procedure was used to define this EI based on a linear combination of DM, WSC and BC of forages at harvest time. The quantitative calculated indexes distinguish five successive ranges of ensilability: high ensilability (EI>+28), medium high ensilability (+9<EI<+28), medium ensilability (-28<EI< +9), medium low ensilability (-47<EI<-28) and low ensilability (EI<-47). This quantitative index was externally evaluated and 100% of samples were successfully classified.